Cutting Edge: Biomarkers for Chronic Spontaneous Urticaria - Marco Folci; Enrico Heffler; Giorgio W. Canonica; Raffaello Furlan; Enrico Brunetta (Journal of Immunology Research)
Chronic spontaneous urticaria (CSU) is defined by the appearance of wheals and a variable presence of angioedema which persists for at least 6 weeks. It represents the most common subtype of chronic urticaria and is gaining importance in civil society because of its association with impaired quality of life. Moreover, CSU has a growing impact on national health systems representing a great burden due to its variable rate of response to the approved therapies. In this scenario, the identification of clinical and molecular biomarkers is of pivotal importance. Some groups are trying to detect molecules which would be able to help clinicians in reaching a proper diagnosis; additionally, the opportunity to describe disease severity which leads to cluster patients in different groups could fill the gap in the numerous unmet clinical needs. Several biomarkers are currently being studied with the purpose to predict the response to a defined therapy; unfortunately, none of them are ready to be translated from bench to bedside.